(untitled) (Pulse, 2015)
Objectives: The aim of this study was to test the hypothesis that decompressive hemicraniectomy (DHC), compared with craniotomy with evacuation of hematoma, and would improve clinical outcomes of patients with supratentorial intracerebral hemorrhage (SICH). Methods: We compared patients (November 2008February 2014) with supratentorial ICH treated with DHC without hematoma evacuation and craniotomy with hematoma evacuation. DHC measured at least 150 mm and included opening of the dura. We analyzed clinical, radiological, and surgical characteristics. Outcome at 6 months was divided into good (modified Rankin Scale 04) and poor (modified Rankin Scale 56). Results: Fifteen patients (mean age 58 years) with ICH were treated by DHC. Median hematoma volume was 61 ml and mean preoperative Glasgow Coma Scale (GCS) was 7. Ten patients had good and five had poor outcomes. In hematoma evacuation group 29 patients were treated. Median hematoma volume was 55 ml and mean preoperative Glasgow Coma Scale (GCS) was 8. Seventeen patients had good and twelve had poor outcomes. Conclusions: DHC is more effective than hematoma evacuation in patients with SICH. Based on this small cohort, DHC may reduce mortality. Larger prospective study is warranted to assess safety and efficacy. Pulse Vol.7 January-December 2014 p.16-21